1983
DOI: 10.1128/iai.39.2.645-654.1983
|View full text |Cite
|
Sign up to set email alerts
|

Effective immunity to dental caries: gastric intubation of Streptococcus mutans whole cells or cell walls induces protective immunity in gnotobiotic rats

Abstract: Gnotobiotic rats were given Streptococcus mutans 6715 whole cells (WC), purified cell walls (CW), or cell wall lysate by gastric intubation (GI), and assessments were made of humoral immune responses in serum and saliva and of caries protection. Levels of secretory immunoglobulin A (IgA) and IgG antibodies to S. mutans WC in saliva samples from experimental rats were determined by an

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
30
0

Year Published

1988
1988
2002
2002

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 37 publications
(34 citation statements)
references
References 21 publications
3
30
0
Order By: Relevance
“…Germ-free (termed gnotobiotic after infection with a specific organism) Fischer rats (CD F(344)GN/Crl BR) used in these studies were bred and maintained in Trexler plastic isolators at the University of Alabama at Birmingham Gnotobiotic Rat Facility (26,28). All experimental rats were maintained in covered sterile cages in a laminar flow hood throughout the experiment and provided cariogenic diet 305 and water ad libitum (26).…”
Section: Animalsmentioning
confidence: 99%
See 2 more Smart Citations
“…Germ-free (termed gnotobiotic after infection with a specific organism) Fischer rats (CD F(344)GN/Crl BR) used in these studies were bred and maintained in Trexler plastic isolators at the University of Alabama at Birmingham Gnotobiotic Rat Facility (26,28). All experimental rats were maintained in covered sterile cages in a laminar flow hood throughout the experiment and provided cariogenic diet 305 and water ad libitum (26).…”
Section: Animalsmentioning
confidence: 99%
“…The basic experimental design used in this study is similar to that reported previously (28). Weanling rats (age 19 to 20 days; 6-7/group) were given 50 |ig of GTF alone or incorporated into various liposome preparations or empty liposomes (control) ( Table 1) by gastric intubation of each preparation in 250 |i,l HBSS buffer on day 0, as previously described (28).…”
Section: Experimental Design For In Vivo Studiesmentioning
confidence: 99%
See 1 more Smart Citation
“…Similar results were obtained for intragastric immunization with whole cells of S. mutans. The antibodies in saliva and serum were primarily directed to serotype g carbohydrate and lipoteichoic acid, the latter being common to many types of streptococcus (23). Thus, the addition of IL-1 in tonsillar immunization appears to have no effect on the antibodies reacting to saccharide antigens either quantitatively or qualitatively.…”
Section: Discussionmentioning
confidence: 93%
“…The antigen mainly responsible in the tonsillar applications was shown to be a serotype saccharide antigen of S. sobrinus (12). In the case of intragastric immunization, the immunization of whole S. sobrinus cells was shown to induce antibodies reacting to some protein antigens (13), as well as the serotype saccharide antigens (23). Although the addition of a mucosal adjuvant in tonsillar applications of killed S. sobrinus cells is expected to increase antibodies in the saliva, it is also important to note the types of antibody, for example antibodies reacting to the serotype saccharide antigens, the protein antigens or both antigens, that may be induced by the addition of the adjuvant.…”
mentioning
confidence: 99%